Trichoderma spp. associado a níveis de adubação NPK no patossistema Sclerotinia sclerotiorum feijoeiro - Rodrigues, Johnathan (2010)
The fungus Sclerotinia sclerotiorum causes major losses in the production of beans. Because it is a soil fungus, it is difficult to control and the biological control with Trichoderma sp. is a viable alternative. There are many factors that can interfere with the performance of the antagonist in biological control, such as pH, amount of water in the soil, soil type and nutrients. The latter are present in abundance in the soil by fertilization performed to meet the needs of the crop, but little is known about their interference in the performance of biological control of S. sclerotiorum by the antagonist Trichoderma sp. Thus, the objectives of this study were to evaluate the influence of NPK (nitrogen, phosphorus and potassium) on the growth of different isolates of Trichoderma sp. and S. sclerotiorum in vitro, as well as the performance of Trichoderma sp. on the in vitro and in vivo control of Sclerotinia sp. and to verify the effect of Trichoderma sp. in the NPK uptake by bean plants. The study was conducted in laboratory and greenhouse in Santa Maria, RS, Brazil. The parameters measured were mycelial growth, sporulation of Trichoderma sp. and percentage of control of the pathogen in vitro. In vivo the incidence of white mold, plant height, root length, leaf number, fresh and dry weight of shoot and root and stem diameter of bean plants were evaluated. The population of Trichoderma sp. in soil and NPK content in plant tissue of the shoot bean were also evaluated. The highest micelial growth was achieved by Trichoderma sp. UFSMT16 for all doses of NPK in vitro, differing from the isolate UFSMT17 only at rates of 75 to 125% of NPK. In the quantification of spores of Trichoderma sp., the isolate UFSMT17 had the highest sporulation in the majority of the different doses of NPK. The isolate UFSMT16 obtained better results in the test of paired cultures, with the highest performance at doses of 50, 75 and 100% NPK (notes 1.00, 1.25 and 1.00, respectively). In the final population, Trichoderma sp. UFSMT15.1 obtained higher CFU g-1 soil (1.3 x 104), differing significantly from the isolate UFSMT16 and the control treatment. For the variable content of phosphorus in plant tissue of the shoot, the interaction between Trichoderma sp. in the absence and presence of S. sclerotiorum associated with doses of NPK, there was statistical difference between the isolates of Trichoderma spp. UFSMT15.1, UFSMT16 and the control treatment at the doses of 25 and 125% of NPK, in the presence and at the dose of 25% in the absence of S. sclerotiorum. It was concluded that the levels of nitrogen, phosphorus and potassium (NPK) in the Elad medium influence growth and reproduction of the genus Trichoderma in vitro; isolates of Trichoderma sp. (UFSMT15.1, UFSMT16, and UFSMT17) have higher growth of colonies in vitro than isolates of S. sclerotiorum, regardless of the dose of NPK; the levels of 25, 50, 75,100 NPK and 125% of the growth medium Elad interfere with effective control of S. sclerotiorum by isolates UFSMT15.1, UFSMT16, and UFSMT17 of Trichoderma sp.; the population of Trichoderma sp. is not affected by varying the application of different doses of NPK in soil and the presence of S. sclerotiorum reduced the height of the aerial parts of beans, even without visible symptoms of the disease, while Trichoderma sp. UFSMT15.1 UFSMT16 and increased in soil with low application of NPK; and UFSMT16 and UFSMT15.1 isolates in the presence and absence of S. sclerotiorum in different levels of NPK interfere with the amount of phosphorus in the shoots of beans, but have no significant effect on the content of nitrogen and potassium.